PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KUALITAS KEHIDUPAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PT.UNITEX TBK DAN PT.PINTU MAS GARMINDO BOGOR - Novi Puspitasari (JURNAL ILMU MANAJEMEN, 2016)
This study aimed to analyze the effect of transformational leadership and quality of work life on employee satisfaction in PT.Unitex Tbk and PT.Pintu Mas Garmindo Bogor. The study involved 120 respondents consisting of 60 employees PT.Unitex Tbk and 60 employees PT.Pintu Mas Garmindo. Analysis of the data used in this research is descriptive analysis and Structural Equation Modelling (SEM) PLS. At both companies showed that transformational leadership and the quality of working life is a significant positive effect on employee job satisfaction, this shows that the higher the value of transformational leadership and the quality of working life, the higher the satisfaction of employees at both companies. The results of this research can be a reference for PT. Unitex Tbk and PT.Pintu Mas Garmindo in increasing employee job satisfaction by implementing transformational leadership style is right for the company and improving the quality of working life.